2010
DOI: 10.1590/s0365-05962010000100020
|View full text |Cite
|
Sign up to set email alerts
|

Caso para diagnóstico

Abstract: HISTÓRIA DA DOENÇACriança branca, 3 anos e 8 meses, apresentou máculas hipopigmentadas e hiperpigmentadas, bilaterais e simétricas, com padrão reticulado no dorso das mãos e pés (Figuras 1 e 2). As lesões se iniciaram no primeiro ano de vida e progrediram lentamente. Não foram precedidas por dermatose inflamatória. Antes da chegada ao nosso hospital, foram diagnosticadas como xeroderma pigmentoso. Ao exame, evidenciamos máculas pigmentadas misturadas às máculas despigmentadas, assintomáticas, no dorso das mãos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…However, histopathological study is not mandatory for the diagnosis. Other pigmentary disorders are included in the differential diagnosis and peculiar features help to distinguish these entities, such as [2]:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, histopathological study is not mandatory for the diagnosis. Other pigmentary disorders are included in the differential diagnosis and peculiar features help to distinguish these entities, such as [2]:…”
Section: Discussionmentioning
confidence: 99%
“…About 20% of the patients do not have a family history, being presumed to have spontaneous mutations [2].…”
Section: Introductionmentioning
confidence: 99%
“…It is often reported in Japanese patients, but there have been also cases in India, Europe, and South America [1, 2]. After the literature review in PubMed database, this is the fourth case reported in Brazil [3, 4]. …”
Section: Introductionmentioning
confidence: 97%